From Tragedy to Renaissance : Improving Agricultural Data for Better Policies - Carletto, Calogero (Taylor and Francis, 2015)
Agricultural development is an essential engine of growth and poverty reduction, yet agricultural data suffer from poor quality and narrow sectoral focus. There are several reasons for this: (1) difficult-to-measure smallholder agriculture is prevalent in poor countries; (2) agricultural data are collected with little coordination across sectors; and (3) poor analysis undermines the demand for high-quality data. This article argues that initiatives like the Global Strategy to Improve Agricultural and Rural Statistics bode well for the future. Moving from Devarajan’s statistical tragedy’ to Kiregyera’s statistical ‘renaissance’ will take a continued long-term effort by individual countries and development partners.